2014
DOI: 10.1001/jamainternmed.2014.674
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide-Induced Autoimmune Hepatitis

Abstract: he incidence and prevalence of diabetes mellitus in the United States is increasing rapidly.1 Eleven unique drug classes have been approved by the US Food and Drug Administration for type 2 diabetes mellitus. 1 Incretin-based hypoglycemic agents, including the glucagon-like peptide 1 (GLP-1) agonists and the dipeptidyl peptidase-4 inhibitors, have recently received considerable press. The US Food and Drug Administration released a statement heightening provider awareness of potential adverse events after data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…In a recent pilot Japanese study, treatment with liraglutide had a good safety profile and significantly improved liver function and histological features in NASH patients with glucose intolerance [70] . A clinical case of suspected liraglutide-induced autoimmune hepatitis has been recently reported [71] . Although caution is required when interpreting the causal relationship of such event [37] , further postmarketing studies are needed to define the hepatotoxic potential of liraglutide and other GLP-1 receptor agonists.…”
Section: Hepatic Safetymentioning
confidence: 99%
“…In a recent pilot Japanese study, treatment with liraglutide had a good safety profile and significantly improved liver function and histological features in NASH patients with glucose intolerance [70] . A clinical case of suspected liraglutide-induced autoimmune hepatitis has been recently reported [71] . Although caution is required when interpreting the causal relationship of such event [37] , further postmarketing studies are needed to define the hepatotoxic potential of liraglutide and other GLP-1 receptor agonists.…”
Section: Hepatic Safetymentioning
confidence: 99%
“…In our literature search, we identified a case of liraglutide-induced autoimmune hepatitis reported by Kern et al; however, the patient's condition did not improve after stopping liraglutide, and the patient eventually needed long-term corticosteroid therapy [ 15 ]. Lack of improvement after discontinuation of the drug in this case suggests autoimmune hepatitis independent of the drug use or liraglutide triggered underlying liver condition [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The LEAD trial compared 48 weeks of subcutaneous liraglutide (1.8 mg/day) to placebo in 52 patients with biopsy-proven non-alcoholic steatohepatitis and was shown to significantly improve steatosis and hepatocyte ballooning on biopsy [84]. The product label of liraglutide does not mention liver injury as an adverse event and only one case report of serious liver injury was reported with liraglutide, which presented as autoimmune hepatitis that did not improve with drug discontinuation [85]. Maor et al reported a case of a 52-year-old female patient with obesity who was treated with liraglutide for weight loss for 3 months [86].…”
Section: Quantitative Systems Pharmacology and Dilimentioning
confidence: 99%